Seasonal Polyphenism and Behavioral Variations of Ceroplastes glomeratus Peronti (Hemiptera: Coccidae) - Rosa, K. C. C.; Peronti, A. L. B. G. [UNESP]; Consoli, F. L.; Sousa-Silva, C. R. (Entomological Soc Brasil, 2017)
The wax scale Ceroplastes glomeratus Peronti shows seasonal behavioral and phenotypic differences. Individuals develop gregariously during autumn, whereas solitarily in spring. Besides such behavioral differences, spring (isolated form) and autumn (aggregated form) will also produce different morphotypes. We provide additional data on the morphological data of the species based on the microscopic and macroscopic characteristics of adult females and of first-instars of the two adult morphotypes of C. glomeratus.
Keywords: Morphology; soft scale; taxonomy; wax scale